Superselective ophthalmic artery fibrinolytic therapy for the treatment of central retinal vein occlusion. Issue 12 (1st December 2000) - Paques, M; Vallée, J N; Herbreteau, D; Aymart, A; Santiago, P Y; Campinchi-Tardy, F; Payen, D; Merlan, J J; Gaudric, A; Massin, P
Abstract : AIM: To study the effect of superselective ophthalmic artery fibrinolysis as a treatment for central retinal vein occlusion (CRVO). METHODS: Retrospective, university based single centre study. The charts of 26 eyes of 26 patients treated were reviewed. Among the 26 patients, there were nine cases of combined artery and vein occlusion, three cases of combined cilioretinal artery and CRVO, and 14 cases of classic CRVO. Complete preoperative and postoperative ophthalmological examination and fluorescein angiography were performed in all cases. The therapeutic procedure comprised the infusion of urokinase through a microcatheter into the ostium of the ophthalmic artery, via a femoral artery approach. The main outcome measure was the improvement in visual acuity 48 hours after the procedure. RESULTS: Six eyes of six patients exhibited significant improvement in visual acuity immediately after the fibrinolysis procedure. Among them, four had a initial funduscopic appearance suggestive of combined occlusion of the central retinal artery (CRAO) and vein. For these patients, the visual benefit was maintained in the long term. Intravitreal haemorrhage occurred in two patients. There were no extraocular complications linked to the procedure. CONCLUSIONS: Selective ophthalmic artery infusion of urokinase was followed by improvement in VA in six out of 26 cases of CRVO. Eyes with combined CRAO and CRVO with recent visual loss appeared to be the most responsive. This treatment did not prevent the occurrence of ischaemia in the failure cases. The efficacy of in situ fibrinolysis for treatment of CRVO needs to be further evaluated in a controlled study.